Phase 1 double-blind randomized safety trial of the Janus kinase inhibitor tofacitinib in systemic lupus erythematosus - Hasni, Sarfaraz A.; Gupta, Sarthak; Davis, Michael; Poncio, Elaine; Temesgen-Oyelakin, Yenealem; Carlucci, Philip M.; Wang, Xinghao; Naqi, Mohammad; Playford, Martin P.; Goel, Rishi R.; Li, Xiaobai; Biehl, Ann J.; et al. (Nature communications, 2021)
Increased risk of premature cardiovascular disease (CVD) is well recognized in systemic lupus erythematosus (SLE). Aberrant type I-Interferon (IFN)-neutrophil interactions contribute to this enhanced CVD risk. In lupus animal models, the Janus kinase (JAK) inhibitor tofacitinib improves clinical features, immune dysregulation and vascular dysfunction. We conducted a randomized, double-blind, placebo-controlled clinical trial of tofacitinib in SLE subjects (ClinicalTrials.gov NCT02535689). In this study, 30 subjects are randomized to tofacitinib (5 mg twice daily) or placebo in 2:1 block. The primary outcome of this study is safety and tolerability of tofacitinib. The secondary outcomes include clinical response and mechanistic studies. The tofacitinib is found to be safe in SLE meeting study’s primary endpoint. We also show that tofacitinib improves cardiometabolic and immunologic parameters associated with the premature atherosclerosis in SLE. Tofacitinib improves high-density lipoprotein cholesterol levels ( p = 0.0006, CI 95%: 4.12, 13.32) and particle number ( p = 0.0008, CI 95%: 1.58, 5.33); lecithin: cholesterol acyltransferase concentration ( p = 0.024, CI 95%: 1.1, −26.5), cholesterol efflux capacity ( p = 0.08, CI 95%: −0.01, 0.24), improvements in arterial stiffness and endothelium-dependent vasorelaxation and decrease in type I IFN gene signature, low-density granulocytes and circulating NETs. Some of these improvements are more robust in subjects with STAT4 risk allele. Increased risk of premature cardiovascular disease in systemic lupus erythematosus (SLE) is not well understood, but in animal models, the Janus kinase inhibitor tofacitinib improves related phenotypes. Here the authors report a Phase 1 double-blind randomized trial that shows tofacitinib is safe and well tolerated in in patients with SLE.